Interleukin levels and their potential association with venous thromboembolism and survival in cancer patients. (9th June 2014) - Reitter, E-M; Ay, C; Kaider, A; Pirker, R; Zielinski, C; Zlabinger, G; Pabinger, I
Summary: Cytokines have been found to be elevated in cancer patients and have been associated with worse prognosis in single tumour entities. We investigated the association of eight different cytokines with venous thromboembolism (VTE) and prognosis in cancer patients. The Vienna Cancer and Thrombosis Study (CATS), a prospective study, includes patients with newly diagnosed tumour or disease progression. Patients with an overt infection are excluded. Study end-points are VTE, death, loss to follow-up or study completion. Interleukin (IL) serum levels were measured using the xMAP technology developed by Luminex. Among 726 included patients, no associations between IL levels and VTE were found, with the exception of a trend for IL-1β and IL-6 in pancreatic cancer. Elevated levels of IL-6 [as continuous variable per double increase hazard ratio (HR) = 1·07, 95% confidence interval (CI) = 1·027–1·114, P = 0·001, IL-8 (HR = 1·12, 95% CI = 1·062–1·170, P < 0·001) and IL-11 (HR = 1·37, 95% CI = 1·103–1·709, P = 0·005] were associated with worse survival. In subgroup analyses based on tumour type, colon carcinoma patients, who had higher IL-6 levels, showed a shorter survival (HR = 2·405, 95% CI = 1·252–4·618, P = 0·008). A significant association of elevated IL-10 levels with a decrease in survival (HR = 1·824, 95% CI = 1·098–3·031, P = 0·020) was seen among patients with lung cancer. No correlation between VTE and IL levels was found, but higher IL-6, IL-8 and IL-11 levels were associated with worse survival in cancer patients. Further, elevated IL-6 levels might be a prognostic marker in colorectal cancer and elevated IL-10 levels in lung cancer patients.